Teacher education for the use of digital technologies: An experience report at Colegio Estadual Professora Luzia Carvalho Silva (Research, Society and Development, 2021)
Teacher training for the use of Digital Technologies of Information and Communication (DTIC) in teaching and learning processes has long been a topic of interest to education researchers, as there is a constant need to understand how this relationship between teacher training and digital technologies can contribute to teaching Of Quality. In the current context, marked by the Covid-19 pandemic, this theme gains even more notoriety, mainly because, unlike non-pandemic times, today, digital technologies are presented as the main means of bringing education to students. Thus, this work aims to present a successful experience on the use of digital technologies by teachers during the Paulo Freire 2020/2021 Pedagogical Journey, at Colegio Estadual Professora Luzia Carvalho Silva in Bahia. As a methodology, we adopted bibliographic research, and the experience report, through which we describe and analyze the socialization of different digital tools by teachers during the opening event of the school year. Based on this experience, the results showed that, despite the teachers' difficulties in teaching using digital technologies, they were open to learning and using some of the resources presented in their remote classes. As a conclusion, it was clear that, in the school space, the exchange of experience among teachers contributes significantly to the improvement of the teaching and learning processes and to a closer relationship between teachers.